2023
DOI: 10.3390/electronics12092070
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Avoidance in Intelligent Transport Networks Based on WSN-IoT through Controlling Data Rate of Zigbee Protocol by Learning Automata

Abstract: Congestion control is one of the primary challenges in improving the performance of wireless sensor networks (WSNs). With the development of this network based on the Internet of Things (IoT), the importance of congestion control increases, and the need to provide more efficient strategies to deal with this problem is strongly felt. This problem is even more important in applications such as Intelligent Transport Systems (ITSs). This article introduces a new method for congestion control in ITSs based on WSN-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The research as well as industrial communities have identified various issues in IoT networks, including heterogeneity, security, congestion, energy efficiency, mobility, reliability, and quality of service, among others [4]. Congestion control has been identified as one of challenges that needs to be addressed in order to keep pace with the steep growth in IoT networks [5,6]. Figure 1 illustrates a typical example of an IoT network.…”
Section: Introductionmentioning
confidence: 99%
“…The research as well as industrial communities have identified various issues in IoT networks, including heterogeneity, security, congestion, energy efficiency, mobility, reliability, and quality of service, among others [4]. Congestion control has been identified as one of challenges that needs to be addressed in order to keep pace with the steep growth in IoT networks [5,6]. Figure 1 illustrates a typical example of an IoT network.…”
Section: Introductionmentioning
confidence: 99%
“…The extremely high density of IoT device connectivity will bring several problems. Congestion is one of the major problems of IoT networks powered by wireless sensor networks (WSNs) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%